Effect of Long-Term use of N95 Masks on Respiratory Gases, Volumes and Capacities of Medical and Paramedical Personnel: A Pilot Study (Global Journal of Medical Research, 2022)
The spread of coronavirus can be greatly reduced by the usage of face coverings as coronavirus is mainly spread through droplets when people talk cough or sneeze and through airborne transmission N95 respirator mask is a protective device which is used to filter out the airborne particles with a very high efficiency which is approximately up to 95 The use of N95 mask in India has increased by a very high proportion due to the on-going coronavirus pandemic
Keywords: statistical knowledge; respiratory volumes and capacities; respiratory gases